The Self in Northern Canadian Hunting Societies: "Cannibals" and Other "Monsters" as Agents of Healing - Ferrara, Nadia; Lanoue, Guy (Anthropologica, 2022)
This paper presents a theory of the Self in northern Canadian hunting societies. Ethnographic arguments are drawn from the Athapaskan-speaking Sekani of northern British Columbia and the Algonquoian-speaking Cree of northern Quebec and Ontario. We describe the three dimensions of the Native "composite" Self in order to discuss Native mechanisms of social and individual inequilibrium and healing. We also attempt to re-analyse the so-called windigo psychosis among the Cree. Like others before us though for very different reasons, we argue that the label "psychosis" misrepresents this phenomenon. The assemblage of beliefs describing the windigo cannibal monster is an important clue for the dynamics by which composite Selves are constructed.